2015
DOI: 10.1038/nature14579
|View full text |Cite
|
Sign up to set email alerts
|

A very luminous magnetar-powered supernova associated with an ultra-long γ-ray burst

Abstract: A new class of ultra-long-duration (more than 10,000 seconds) γ-ray bursts has recently been suggested. They may originate in the explosion of stars with much larger radii than those producing normal long-duration γ-ray bursts or in the tidal disruption of a star. No clear supernova has yet been associated with an ultra-long-duration γ-ray burst. Here we report that a supernova (SN 2011kl) was associated with the ultra-long-duration γ-ray burst GRB 111209A, at a redshift z of 0.677. This supernova is more than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
341
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(362 citation statements)
references
References 38 publications
15
341
2
4
Order By: Relevance
“…Magnetars have also been suggested to explain lGRBs (see previous subsection). However, present simulations lead rather to a strong r-process and negligibe amounts of Ni-ejecta (supported by light curve observations being powered by pulsar emission rather than 56 Ni decay [19]). …”
Section: Long Duration Gamma-ray Bursts and Hypernovaesupporting
confidence: 73%
See 2 more Smart Citations
“…Magnetars have also been suggested to explain lGRBs (see previous subsection). However, present simulations lead rather to a strong r-process and negligibe amounts of Ni-ejecta (supported by light curve observations being powered by pulsar emission rather than 56 Ni decay [19]). …”
Section: Long Duration Gamma-ray Bursts and Hypernovaesupporting
confidence: 73%
“…Recent observations [19] underline that there exist core-collapse supernova explosions whose light curves are not determined by (large) amounts of 56 Ni ejecta, but rather by the energy release of a fast rotating neutron star (pulsar) with extremely strong magnetic fields of the order 10 15 Gauss (magnetars). The question is how can neutron stars of such extremely high magnetic fields (in comparison to the typical 10 12 Gauss) emerge from supernova explosions.…”
Section: The Effect Of Strong Magnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examine SNLS-06D4eu (Howell et al 2013), the most distant spectroscopically confirmed published SLSN to date (Section 5). We then compare the results with a line-poor, luminous SN 2011kl/GRB111209A (Greiner et al 2015) in Section 6. We conclude with a discussion of the general properties of SLSN spectra, and the inferences that can be made about these events from their spectral properties (Section 7).…”
Section: Introductionmentioning
confidence: 99%
“…SN 2011kl represents the first SLSN associated with an ultra long GRB [11]. This gamma-ray burst lasted several hours whereas the typical long-duration GRBs (LGRBs) fade in a matter of minutes.…”
Section: Magnetar Driven Supernovaementioning
confidence: 99%